Positive electrode material, positive electrode sheet, electrochemical device and electric device
By interspersing carbon nanotubes into the agglomerates of lithium manganese iron phosphate positive electrode material and optimizing structural parameters, the problem of poor conductivity inside the agglomerates is solved, the cycle performance and fast charging performance of the battery are improved, and the energy density is achieved. Kinetics performance.
Patent Information
- Application Number
- CN202411305487.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The poor conductivity and low diffusion rate of lithium manganese iron phosphate (LMFP) cathode materials affect their discharge capacity, rate performance and cycling performance, especially the problem of insufficient conductivity inside the agglomerate.
Using agglomerates with the chemical formula LiMnxFeyM(1-x-y)PO4, the relationship between manganese molar ratio, porosity, and CNT length and primary particle diameter is optimized by interspersing carbon nanotubes (CNTs) into the agglomerates to ensure 0.09≤a*c /b≤126 to improve internal conductivity and structural stability.
It effectively improves the conductivity and cycling performance of the positive electrode material, takes into account the fast charging performance and energy density of the battery, reduces the impedance, and enhances the dynamic performance and structural stability of lithium ions.
Smart Images

Figure CN118867204B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of positive electrode materials, and in particular to a positive electrode material, a positive electrode sheet, an electrochemical device and an electrical device. Background Art
[0002] Lithium manganese iron phosphate (LMFP) cathode material has attracted wide attention in the field of electric vehicles and portable electronic devices due to its high energy density. Compared with lithium iron phosphate (LFP), LMFP increases the theoretical energy density of the battery by introducing manganese elements, making the battery have a longer battery life.
[0003] However, LMFP materials have problems such as poor conductivity and extremely low lithium ion diffusion rate, which affect their discharge capacity, rate performance, cycle performance, etc. At present, in order to improve its conductivity, the particle size of LMFP materials is often reduced, but when the particle size of LMFP is too small, the surface density cannot be increased; there are some methods to make manganese iron lithium into agglomerates, which can increase its surface density, but the currently disclosed manganese iron lithium agglomerates have the problem of poor internal conductivity, which in turn causes insufficient internal kinetic transmission. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of the agglomerates disclosed in the prior art that the internal conductivity is poor, resulting in insufficient internal kinetic transmission, thereby providing a positive electrode material, positive electrode sheet, electrochemical device and electrical device that solve the above problem.
[0005] To achieve the above object, the present invention provides a positive electrode material, including a chemical formula of LiMn x Fe y M (1-x-y) Agglomerates of PO4, wherein 0.5≤x<1, 0<y≤0.5; the agglomerates include primary particles and carbon nanotubes between the primary particles; the agglomerates satisfy the following relationship:
[0006] 0.09≤a*c / b≤126; b=L CNT / d;
[0007] Wherein, a is the molar ratio of manganese in the aggregate to the total amount of ferromanganese; c is the porosity of the aggregate, in units of %; d is the diameter of the primary particle, in units of nm; L CNT is the average length of carbon nanotubes in the aggregate, in nm.
[0008] The present invention also provides a positive electrode sheet, comprising the positive electrode material mentioned above.
[0009] The present invention provides an electrochemical device, comprising the positive electrode sheet.
[0010] The present invention provides an electrical device, comprising the electrochemical device mentioned above.
[0011] The beneficial effects of the present invention are:
[0012] The positive electrode material disclosed in the present invention is LiMn by optimizing the chemical formula x Fe y M (1-x-y) The structure of PO4 agglomerates, interspersing carbon nanotubes (CNTs) inside the agglomerates instead of just wrapping them on the surface of the agglomerates, can effectively improve the conductivity inside the particles, thereby providing a prerequisite for obtaining batteries with better performance. The above-mentioned interspersing means that CNTs can be set between primary particles and primary particles, or between several primary particles. In the present invention, in order to obtain a battery with a higher energy density, the higher the manganese molar ratio a value, the better; at the same time, the increase in b value can improve the conductivity; the increase in porosity c can improve the wetting performance of the electrolyte on the material. However, if the manganese molar ratio a is too high and the porosity c is too large, the conductivity inside the agglomerate will be poor, the impedance will increase, the internal kinetic performance of the agglomerate will be poor, and the fast charging performance of the battery will be affected. In addition, if the manganese molar ratio is too high, the structural stability of the agglomerate will deteriorate, the risk of manganese dissolution will increase, and the cycle performance will deteriorate. Therefore, the present invention can improve the internal conductivity of the agglomerate, reduce impedance, and improve the kinetic performance of lithium ions by comprehensively adjusting the relationship between a, c and b, while improving the structural stability of the agglomerate and the cycle performance. In particular, by controlling 0.09≤a*c / b≤126, a positive electrode material with better internal conductivity and more stable agglomerate structure can be obtained, which has a relatively high energy density while taking into account both the fast charging performance and the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 3 is a SEM image of the agglomerates in Example 1 of the present invention at a magnification of 5.00K, where 5.00K is 5000.
[0015] Figure 2 : is a SEM picture of the agglomerates in Example 1 of the present invention at a magnification of 20.00K, where 20.00K is 20,000.
[0016] Figure 33 is a SEM image of the agglomerates in Example 1 of the present invention at a magnification of 50.00K, where 50.00K is 50,000. DETAILED DESCRIPTION
[0017] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0018] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0019] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 50%-90% and 60%-80% is listed for a particular parameter, it is understood that the range of 50% to 80% and 60% to 90% is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0.5-4" means that all real numbers between "1-4" have been listed in this article, for example: 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, etc. "0.5-4" is just an abbreviation of these numerical combinations.
[0020] The present invention provides a positive electrode material, including a LiMn x Fe y M (1-x-y) Agglomerates of PO4, wherein 0.5≤x<1, 0<y≤0.5; M is a doping element, x+y≤1; the agglomerates include primary particles and carbon nanotubes between the primary particles; the agglomerates satisfy the following relationship:
[0021] 0.09≤a*c / b≤126;
[0022] Specifically, a is the molar ratio of manganese in the aggregate to the total amount of ferromanganese;
[0023] c is the porosity of the aggregate, unit is %;
[0024] b=L CNT / d; where d is the diameter of the primary particle, in nm; L CNT is the average length of carbon nanotubes CNT in the agglomerates, in nm; by comprehensively adjusting the relationship between the average length of carbon nanotubes CNT and the diameter of primary particles, the internal conductivity of the agglomerates is improved and the internal dynamic performance of the agglomerates is enhanced.
[0025] Aggregate: refers to a secondary particle in an agglomerated state formed by the aggregation of two or more primary particles. The agglomerated state of the primary particles can be observed by using a scanning electron microscope (SEM).
[0026] Porosity: The porosity inside the agglomerate. The porosity reflects the degree of stacking of primary particles inside the agglomerate.
[0027] The present invention optimizes the chemical formula to be LiMn x Fe y M (1-x-y) The structure of PO4 agglomerates, interspersing carbon nanotubes inside the agglomerates instead of just wrapping them on the surface of the agglomerates, can effectively improve the conductivity inside the particles, thereby providing the prerequisite for obtaining batteries with better performance.
[0028] In order to obtain a battery with higher energy density, the present invention has a higher manganese molar ratio a, the better; at the same time, the increase in the value of b can improve the conductivity; the increase in the value of porosity c can improve the wettability of the electrolyte to the material. However, if the manganese molar ratio a is too high and the porosity c is too large, it will cause poor conductivity and increased impedance inside the agglomerate, poor dynamic performance inside the agglomerate, and affect the fast charging performance of the battery; in addition, if the value of manganese molar ratio a is too high, the structural stability of the agglomerate will deteriorate, the risk of manganese dissolution will increase, and the cycle performance will deteriorate. By controlling the value of b to be larger and using CNT to intersperse inside the agglomerate, it is not only possible to improve the conductivity, reduce impedance, and improve the dynamic performance of lithium ions; it is also possible to stabilize the agglomerate structure, improve structural stability, and increase battery cycle stability.
[0029] Therefore, the present invention can improve the internal conductivity of the agglomerate, reduce impedance, and improve the kinetic performance of lithium ions by comprehensively adjusting the relationship between a, c and b; at the same time, the structural stability of the agglomerate is improved and the cycle performance is improved; in particular, by controlling 0.09≤a*c / b≤126, a positive electrode material with better internal conductivity and more stable agglomerate structure can be obtained, effectively taking into account the fast charging performance and cycle performance of the battery.
[0030] Specifically, the higher the manganese molar ratio a, the worse the internal conductivity of the agglomerate, and at the same time, the structural stability of the agglomerate deteriorates, the risk of manganese dissolution increases, and the cycle performance deteriorates; the larger the porosity c, the larger the gap between the primary particles, and CNTs are needed to electrically connect and improve the structural stability of the agglomerate; that is, when the manganese molar ratio is high and / or the porosity is large, the value of b can be adjusted, that is, L can be regulated. CNT The relationship between a*c / b and the diameter of the primary particles is used to improve the conductivity and improve the structural stability of the agglomerates. The present invention has found that when a*c / b is higher than 126, there may be a problem of slow kinetic transmission rate due to poor internal conductivity of the material; there may also be problems of poor structural stability of the agglomerates, increased risk of manganese dissolution, and attenuated cycle performance. The present invention effectively achieves the purpose of taking into account both the fast charging performance and cycle stability of the battery by controlling a*c / b not to exceed 126.
[0031] At the same time, the present invention has also found that the value of a*c / b should not be too low. When the b value is large, although the conductivity inside the agglomerate may be improved, a b value that is too high indicates that the CNT length is too long, and / or the primary particle size is too small, and the CNT or primary particles inside the agglomerate are too densely packed, resulting in obstructed lithium ion transmission, increased ionic impedance, and deteriorated kinetic performance. The manganese molar ratio a is too low, which affects the average voltage and leads to low energy density of the battery. The porosity c is too low, the degree of tightness between the primary particles is high, the electrolyte infiltration efficiency is poor, the lithium ion transmission rate is affected, and the fast charging performance of the battery is reduced. When a*c / b is lower than 0.09, there will be problems of low energy density and poor fast charging performance. The present invention effectively achieves the purpose of taking into account both fast charging performance and energy density of the battery by controlling a*c / b to be not less than 0.09.
[0032] In summary, by controlling a*c / b within a certain range (0.09≤a*c / b≤126), a positive electrode material with better internal conductivity can be obtained while taking into account the fast charging performance and energy density of the battery. In the present invention, the value of a*c / b can be any value between 0.09-126, for example: 0.09, 0.1, 0.3, 0.5, 1, 3, 5, 7, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 126, etc.
[0033] Furthermore, by controlling the value of a*c / b within a more preferred range of 0.6-20, the internal dynamic transmission performance of the present invention is better.
[0034] The present invention further optimizes the molar ratio a of manganese in the total amount of ferromanganese in the agglomerates; if the a value is too low, the manganese content is low, which affects the average voltage and has a low energy density; if the a value is too high, the manganese content is too high, which leads to poor kinetic performance, poor structural stability of the agglomerates, increased risk of manganese dissolution, and poor cycle performance; therefore, in the present invention, the range of a is 0.5-0.96, preferably 0.6-0.85. For example: control the a to be 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.96, etc.
[0035] The present invention further optimizes the porosity c of the agglomerates; if the c value is low, the porosity is too low, which affects the electrolyte infiltration and contact inside the primary particles; if the c value is high, the porosity is large, resulting in poor conductive contact between particles; therefore, the unit of the porosity c of the agglomerates in the present invention is %, and the value of c is 5-35, preferably 10-25; for example: the porosity c is controlled to be 5, 10, 12, 15, 20, 25, 30, 35, etc.
[0036] The porosity c of the agglomerates is affected by parameters such as solid content, flow rate, pressure, etc. in the spray drying process. In the present invention, the porosity of the agglomerates can be adjusted by adjusting the solid content.
[0037] The present invention further optimizes the range of b, that is, controls the value of b to be 0.25-50, preferably 1-13, which can further improve the internal kinetic transmission capacity. Specifically, if the CNT length is too long and / or the size of the primary particles is too small, the CNT or primary particles inside the agglomerate are too densely packed, lithium ion transmission is blocked, resulting in increased ion impedance, deteriorated kinetic performance, and poor cycle performance; while if the CNT length is too short and the size of the primary particles is too large, the function of improving the internal conductivity of the agglomerate cannot be achieved; therefore, when the diameter of the primary particles is relatively small, the primary particles inside the agglomerate are densely packed, and the distance between two adjacent primary particles is small, L CNT Can be controlled to be smaller by controlling L CNT The value of / d is in the range of 0.25-50, so that it can achieve the purpose of internal conductivity while avoiding the increase of ion transmission impedance, ensuring sufficient kinetic transmission capacity inside the particles and improving the conductivity.
[0038] Furthermore, the L CNT 100nm-1000nm, preferably 200nm-800nm; for example: L CNT It is 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, etc.
[0039] And / or, the diameter d of the primary particle is 20nm-400nm, preferably 40nm-200nm; for example: the diameter d of the primary particle is 20nm, 30nm, 40nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, etc.
[0040] The above L CNT The length and diameter d of the primary particles are related to the process conditions for preparing the positive electrode material. In the present invention, for example, the grinding time and rotation speed can be adjusted to adjust the L CNT length and diameter d of the primary particle.
[0041] The invention also discloses a positive electrode sheet, comprising the positive electrode material mentioned above.
[0042] Furthermore, the positive electrode sheet also includes a positive electrode conductive agent, which is selected from conductive carbon black and carbon nanotubes; the carbon nanotubes include one or more of multi-walled carbon nanotubes MWCNT, single-walled carbon nanotubes SWCNT, and carbon nanotube fibers VGCF, and the conductive carbon black can be selected from Ketjen black KB. Preferably, the positive electrode conductive agent is selected from conductive carbon black. In the present invention, conductive carbon black is preferably added, and the gaps between the agglomerates are filled with conductive carbon black, so as to achieve a better effect of ensuring wetting and conductive transmission.
[0043] Hereinafter, an embodiment of a positive electrode material, a positive electrode sheet, an electrochemical device, and an electrical device of the present invention will be specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] [Electrochemical device]
[0045] The electrochemical device in the present invention is a secondary battery, also known as a rechargeable battery or storage battery, which refers to a battery that can be recharged to activate the active material after the battery is discharged and continue to be used.
[0046] Normally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.
[0047] As an example, the preparation process of a secondary battery is as follows: stack the positive electrode sheet, the isolation film, and the negative electrode sheet in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and obtain a secondary battery through vacuum packaging, standing, formation, shaping and other processes.
[0048] [Positive electrode]
[0049] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material, and the positive electrode active material is any positive electrode material disclosed in the present invention.
[0050] As an example, the positive electrode material in the present invention includes LiMn x Fe y M (1-x-y) Aggregates of PO4; the aggregates include primary particles and carbon nanotubes between the primary particles.
[0051] The preparation method of the positive electrode material is: using a solid phase grinding method or a hydrothermal reaction method to obtain a LiMn x Fe y M (1-x-y) PO4 precursor slurry, and then the precursor slurry is mixed with the coated carbon source and carbon nanotube conductive slurry, ground and spray-dried to obtain dry powder; the dry powder is sintered under a protective atmosphere, and after cooling, a lithium manganese iron phosphate positive electrode material with CNT formed inside the agglomerate is obtained.
[0052] Among them, the process of preparing precursor slurry by solid phase grinding method to obtain positive electrode material is as follows: weigh the required lithium source, manganese source, iron source and phosphorus source in molar ratio and add deionized water, and perform the first grinding to obtain precursor slurry; add coated carbon source and carbon nanotube conductive slurry to the precursor slurry and mix them evenly, and perform the second grinding; adjust the solid content and spray dry to obtain dry powder; sinter the dry powder under a protective atmosphere, and obtain lithium manganese iron phosphate positive electrode material with CNT formed inside the agglomerate after cooling.
[0053] The process of preparing precursor slurry by hydrothermal reaction method to obtain positive electrode material is as follows: weigh the manganese source and iron source required for synthesizing precursor slurry in molar ratio, add them to the reactor, add deionized water, and react; add lithium source and phosphorus source to the reactor, and continue to react after adding; adjust pH and heat to reaction temperature, and obtain reaction slurry after reaction; filter the reaction slurry with a centrifuge and wash with water, and the solid component after washing is lithium iron manganese phosphate intermediate powder, and grind the lithium iron manganese phosphate intermediate powder for the first time to obtain precursor slurry. Finally, add the precursor slurry, coated carbon source, and carbon nanotube conductive slurry to a mixing tank, add deionized water and mix, and then enter the sand mill for the second grinding to obtain slurry, transfer the slurry to the pre-spray storage tank, adjust the solid content of the slurry, and spray dry to obtain dry powder; sinter the dry powder under a protective atmosphere, and obtain lithium iron manganese phosphate positive electrode material with CNT formed inside the agglomerate after cooling.
[0054] At the same time, when preparing the precursor slurry, a certain amount of doping elements (i.e., chemical formula LiMn x Fe y M (1-x-y) The M in PO4 is mixed with a manganese source, an iron source, a phosphorus source, and a lithium source, and the doping elements are one or more of vanadium, tungsten, titanium, magnesium, etc. The sources of the doping elements are such as vanadium source (vanadium pentoxide), tungsten source (ammonium metatungstate), titanium source (titanium oxide), magnesium source (magnesium carbonate), etc., to obtain a precursor slurry containing a certain amount of doping elements.
[0055] The present invention adopts the above preparation method to realize the preparation of positive electrode material, and the positive electrode material includes LiMn x Fe y M (1-x-y) CNT aggregates are formed inside PO4.
[0056] Among them, the lithium source, manganese source, iron source, phosphorus source and doping elements of the positive electrode material are selected from one or more materials of lithium carbonate, lithium hydroxide, manganese carbonate, manganese oxide, manganese oxalate, iron phosphate, magnesium oxide, lithium dihydrogen phosphate, ferrous oxalate and diammonium hydrogen phosphate.
[0057] In the preparation method of the positive electrode material of the present invention, the diameter d of the primary particles is related to the parameters such as the time and rotation speed of the first grinding, and the length L of the carbon nanotubes is CNT It is related to the parameters such as the rotation speed and time of the second grinding. The diameter d of the primary particles and the length L of the carbon nanotubes can be adjusted by changing the parameters of the first and second grinding. CNT .
[0058] The grinding time of the first grinding can be selected as 1-4h, for example: the grinding time is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc.; the grinding speed of the first grinding can be selected as 400-700r / min.
[0059] The grinding time of the second grinding can be selected as 0.5-4h, for example: the grinding time is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc.; the grinding speed of the second grinding can be selected as 250-600r / min, for example: the grinding speed is 250r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min, etc.
[0060] The porosity of the agglomerates in the positive electrode material obtained by spray drying is affected by the solid content. Therefore, the solid content of the slurry for spray drying can be selected to be 20%-60%, for example: the solid content is 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%.
[0061] In the hydrothermal reaction method, the pH value after pH adjustment can be selected to be 5-7, for example: the pH value is 5, 6 or 7.
[0062] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling, cutting and other processes, the positive electrode sheet can be obtained.
[0063] In the present invention, the binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. In the present invention, the binder can be a conventional choice in the battery field. Specifically, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.
[0064] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.
[0065] [Negative electrode]
[0066] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material. As an example, the negative electrode active material includes natural graphite, artificial graphite, mesophase carbon microspheres, hard carbon, soft carbon, silicon, SiOx, silicon carbon, Li4Ti5O 12 One or more of .
[0067] In some embodiments, the negative electrode film layer may optionally include a conductive agent; as an example, the conductive agent may be selected from conductive carbon black.
[0068] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling, cutting and other processes, the negative electrode sheet can be obtained.
[0069] In some embodiments, as an example, the negative electrode current collector is a copper foil.
[0070] [Electrolyte]
[0071] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present invention has no specific restrictions on the type of electrolyte, which can be selected according to needs. As an example, the electrolyte of the present invention can be various electrolytes suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt.
[0072] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5-5 mol / L.
[0073] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0074] [Isolation film]
[0075] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0076] In some embodiments, as an example, the separator is one of PP, PE, and PP / PF.
[0077] Example 1
[0078] An electrochemical device, such as a secondary battery, includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte.
[0079] 1. Preparation of positive electrode
[0080] The specific preparation process of the positive electrode sheet is as follows: obtain the positive electrode active material, mix the positive electrode active material, conductive carbon black, binder PVDF, and carbon nanotube conductive agent in a mass ratio of 96.5:1:2:0.5, add solvent NMP, stir until the system is uniform under the action of a vacuum mixer, and obtain a positive electrode slurry with a solid content of 55%; coat the positive electrode slurry on an aluminum foil to obtain a double-sided coated positive electrode sheet; then dry, roll, and cut to obtain a positive electrode sheet. The SEM images of the agglomerates in the positive electrode sheet at different magnifications in the present invention are as follows Figure 1-Figure 3 shown.
[0081] The process of obtaining the positive electrode active material is as follows:
[0082] 1.1. Solid phase grinding: First, based on the synthesis of lithium iron manganese phosphate material LiMn 0.9 Fe 0.1According to the molar ratio requirements of lithium source, manganese source, iron source and phosphorus source required by PO4 theory, lithium carbonate, manganese oxide, iron phosphide and diammonium hydrogen phosphate were weighed respectively, and the raw materials were placed in the premixing tank of the sand mill. After mixing, deionized water was added to reach a solid content of 20%. 0.5mm zirconia balls were used as grinding media. The first grinding time was 0.5h and the grinding speed was 650 r / min to obtain a precursor slurry.
[0083] 1.2. Spray drying: Add 20% of the solid mass of glucose in the precursor slurry as a coating carbon source. At the same time, add 0.6% of the solid mass of carbon nanotube conductive slurry in the precursor slurry (the solid content of the carbon nanotube conductive slurry is 4%), mix evenly with the aforementioned precursor slurry, and then grind for the second time at a grinding speed of 500 r / min for 4 hours, adjust the solid content to 21.4%, and set the spray drying speed to 65 L / min for spray drying.
[0084] 1.3. High-temperature sintering: The dried powder was transferred to a tubular sintering furnace, heated to 650°C at a heating rate of 5°C / min under a nitrogen atmosphere, sintered at 650°C for 6 hours, and naturally cooled to room temperature to obtain a lithium manganese iron phosphate positive electrode material with CNTs formed inside the agglomerate.
[0085] 2. Preparation of negative electrode sheet
[0086] The specific preparation process is: graphite, conductive carbon black, thickener CMC, and binder SBR are mixed evenly in a mass ratio of 96.4:1:1.2:1.4, dispersed in deionized water to obtain a negative electrode slurry; the negative electrode slurry is coated on a copper foil to obtain a double-sided coated electrode sheet; then rolling and cutting are performed to obtain a negative electrode sheet.
[0087] 3. Obtaining the isolation film
[0088] The isolation film in this embodiment is a PP isolation film.
[0089] 4. Preparation of electrolyte
[0090] The specific preparation process is: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0091] 5. Assembly of secondary batteries
[0092] The specific process is: stack the above-mentioned positive electrode sheet, isolation film, and negative electrode sheet in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and obtain a lithium-ion secondary battery through vacuum packaging, standing, forming, shaping and other processes.
[0093] Example 2
[0094] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0095] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 5:5. The first grinding time is 4 hours, the first grinding speed is 650r / min, the second grinding time is 1 hour, the second grinding speed is 300r / min, and the solid content of the slurry is adjusted to 45.5% before spraying.
[0096] Example 3
[0097] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1. Specifically, the process of obtaining the positive electrode active material in this embodiment is:
[0098] 1.1. Hydrothermal reaction method: First, based on the synthesis of lithium iron manganese phosphate material LiMn 0.8 Fe 0.2 According to the molar ratio required by PO4 theory, lithium carbonate, manganese oxide, iron phosphide, and diammonium phosphate are weighed separately, manganese oxide and iron phosphide are added to the reactor, deionized water is added to react for 1 hour, and then lithium carbonate and diammonium phosphate are added to the reactor. After the addition is completed, the reaction is continued for 1 hour. Add an appropriate amount of 5% sodium hydroxide solution to adjust the pH to 6, increase the reactor temperature to 90°C, and terminate the reaction after 6 hours. Filter the reaction slurry with a centrifuge, wash with water, and the washed solid component is LiMn 0.8 Fe 0.2 PO4 intermediate powder. 0.8 Fe 0.2 Deionized water was added to the PO4 intermediate powder to reach a solid content of 20%, and a 0.5 mm zirconia ball was used as a grinding medium for the first grinding. The first grinding time was 2.0 h and the grinding speed was 400 r / min to obtain a precursor slurry.
[0099] 1.2. Spray drying: weigh glucose according to 20% of the solid mass in the precursor slurry and weigh CNT conductive slurry according to 0.6% of the solid mass (the solid content of CNT conductive slurry is 4%), add them into the mixing tank, add deionized water and mix, then put them into the sand mill, adjust the speed of the sand mill to 400 rpm, grind for 3 hours, transfer the slurry into the pre-spray storage tank, adjust the solid content of the slurry to 30%, set the spray drying speed to 65L / min for spray drying.
[0100] 1.3. High temperature sintering: The dried powder was transferred to a tubular sintering furnace, heated to 650°C at a heating rate of 5°C / min in a nitrogen atmosphere, sintered at 650°C for 6 hours, and naturally cooled to room temperature to obtain LiMn agglomerates with CNTs formed inside. 0.8 Fe 0.2 PO4 powder.
[0101] Example 4
[0102] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0103] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 6:4. The first grinding time is 3h, the first grinding speed is 680r / min, the second grinding time is 2h, the second grinding speed is 400r / min, and the solid content of the slurry is adjusted to 40.5% before spraying.
[0104] Example 5
[0105] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0106] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 3:1. The first grinding time is 3h, the first grinding speed is 650r / min, the second grinding time is 3h, the second grinding speed is 400r / min, and the solid content of the slurry is adjusted to 38.5% before spraying.
[0107] Example 6
[0108] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0109] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 6:4. The first grinding time is 2.8 h, the first grinding speed is 650 r / min, the second grinding time is 1.5 h, the second grinding speed is 350 r / min, and the solid content of the slurry is adjusted to 42.8% before spraying.
[0110] Example 7
[0111] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0112] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 24:1. The first grinding is 3 hours, the first grinding speed is 680r / min, the second grinding time is 1 hour, the second grinding speed is 380r / min, and the solid content of the slurry is adjusted to 23.2% before spraying.
[0113] Example 8
[0114] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0115] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 17:3. The first grinding is 2.5 hours, the speed of the first grinding is 500r / min, the second grinding time is 3.8 hours, the speed of the second grinding is 500r / min, and the solid content of the slurry is adjusted to 28.5% before spraying.
[0116] Example 9
[0117] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0118] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 13:7. The first grinding is 0.5h, the speed of the first grinding is 500r / min, the second grinding time is 4h, the speed of the second grinding is 550r / min, and the solid content of the slurry is adjusted to 20% before spraying.
[0119] Example 10
[0120] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0121] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 11:9. The first grinding is 2h, the speed of the first grinding is 400r / min, the second grinding time is 4h, the speed of the second grinding is 500r / min, and the solid content of the slurry is adjusted to 47.5% before spraying.
[0122] Embodiment 11
[0123] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this embodiment is different, and the rest is exactly the same as Example 1, specifically:
[0124] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 49:1. The first grinding is 1 hour, the first grinding speed is 300r / min, the second grinding time is 2 hours, the second grinding speed is 350r / min, and the solid content of the slurry is adjusted to 15.2% before spraying.
[0125] Example 12
[0126] A secondary battery, which is different from Example 6 only in that metal is doped during the process of obtaining the positive electrode active material in this embodiment, and the rest is the same as Example 6, specifically:
[0127] The total molar amount of ferromanganese in the precursor slurry is the same, and the manganese source and the iron source are fed at a molar ratio of 24:1. During the feeding process, doping elements accounting for 2000ppm of the total molar mass of ferromanganese are mixed with the manganese source, iron source, phosphorus source, and lithium source, and the source of the doping element is vanadium pentoxide. The first grinding is 3h, the speed of the first grinding is 680r / min, the second grinding time is 1h, the speed of the second grinding is 380r / min, and the solid content of the slurry is adjusted to 20.4% before spraying.
[0128] Example 13
[0129] A secondary battery, which is different from Example 1 only in that the carbon nanotube conductive agent used in the positive electrode sheet of this embodiment is replaced by conductive carbon black, and the process of obtaining the positive electrode active material is different. The rest is exactly the same as Example 1, specifically:
[0130] The total molar amount of manganese and iron in the precursor slurry is the same, and the manganese source and iron source are added in a molar ratio of 41:9. The first grinding is 2h, the first grinding speed is 400r / min, the second grinding time is 3h, the second grinding speed is 400r / min, and the solid content of the slurry is adjusted to 26.4% before spraying.
[0131] Comparative Example 1
[0132] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this comparative example is different, and the rest is exactly the same as Example 1, specifically:
[0133] Compared with Example 1, the manganese source and iron source of the lithium manganese iron phosphate precursor are fed in a molar ratio of 24:1. The first grinding is 0.5 h, the speed of the first grinding is 650 r / min, the second grinding time is 4 h, the speed of the second grinding is 500 r / min, and the solid content of the slurry is adjusted to 19.4% before spraying.
[0134] Comparative Example 2
[0135] A secondary battery, which is different from Example 1 only in that the process of obtaining the positive electrode active material in this comparative example is different, and the rest is exactly the same as Example 1, specifically:
[0136] Compared with Example 1, the manganese source and iron source of the lithium manganese iron phosphate precursor are fed in a molar ratio of 6:4, the first grinding is 4 hours, the first grinding speed is 650r / min, the second grinding time is 0.8h, the second grinding speed is 280r / min, and the solid content of the slurry is adjusted to 49.5% before spraying.
[0137] Comparative Example 3
[0138] A secondary battery, which is different from Example 1 only in that CNT is not added in the process of obtaining the positive electrode active material in this comparative example, and the rest is exactly the same as Example 1. The specific process is as follows:
[0139] 1. Preparation of positive electrode
[0140] The specific preparation process of the positive electrode sheet is as follows: obtain the positive electrode active material, mix the positive electrode active material, conductive carbon black, binder PVDF, and carbon nanotube conductive agent in a mass ratio of 96.5:1:2:0.5, add solvent NMP, and stir under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry with a solid content of 55%; coat the positive electrode slurry on aluminum foil to obtain a double-sided coated positive electrode sheet; and then dry, roll, and cut to obtain a positive electrode sheet.
[0141] The process of obtaining the above positive electrode active material is as follows:
[0142] 1.1. Solid phase grinding: First, based on the synthesis of lithium iron manganese phosphate material LiMn 0.8 Fe 0.2According to the molar ratio requirements of lithium source, manganese source, iron source and phosphorus source required by PO4 theory, lithium carbonate, manganese oxide, iron phosphide and diammonium hydrogen phosphate were weighed respectively and placed in the premixing tank of the sand mill. After mixing, deionized water was added to reach a solid content of 20%. 0.5mm zirconia balls were used as grinding media. The first grinding was 0.5h at a grinding speed of 650 r / min to obtain a precursor slurry.
[0143] 1.2. Spray drying: Add 20% of the solid mass of glucose in the precursor slurry as a coating carbon source, mix it evenly with the aforementioned precursor slurry, and then grind it at a grinding speed of 500 r / min for 4 hours, adjust it to a solid content of 23.6%, and set the spray drying speed to 65 L / min for spray drying.
[0144] 1.3. High temperature sintering: The dried powder was transferred to a tubular sintering furnace, heated to 650°C in a nitrogen atmosphere, sintered at 650°C for 6 hours, and naturally cooled to room temperature to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.
[0145] 2. Preparation of negative electrode sheet
[0146] The specific preparation process is: graphite: conductive carbon black, thickener CMC, binder SBR are mixed evenly in a mass ratio of 96.4:1:1.2:1.4, dispersed in deionized water to obtain negative electrode slurry; the negative electrode slurry is coated on copper foil to obtain a double-sided coated electrode sheet; then roll and cut to obtain a negative electrode sheet.
[0147] 3. Obtaining the isolation film
[0148] The isolation film in this embodiment is a PP isolation film.
[0149] 4. Preparation of electrolyte
[0150] The specific preparation process is: ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0151] 5. Assembly of secondary batteries
[0152] The specific process is: stack the above-mentioned positive electrode sheet, isolation film, and negative electrode sheet in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wind them to obtain a bare battery cell; place the bare battery cell in an outer packaging shell, inject electrolyte after drying, and obtain a lithium-ion secondary battery through vacuum packaging, standing, forming, shaping and other processes.
[0153] Comparative Example 4
[0154] A secondary battery, which is different from Example 1 only in that, in this comparative example, CNT is not added to the lithium manganese iron phosphate material during the process of obtaining the positive electrode active material, but is directly prepared on the particle surface of the lithium manganese iron phosphate material. The specific preparation process is as follows:
[0155] Obtaining lithium iron manganese phosphate materials: (1) Based on the synthesis of lithium iron manganese phosphate materials LiMn 0.9 Fe 0.1 According to the molar ratio requirement of lithium source, manganese source, iron source and phosphorus source required by PO4 theory, lithium carbonate, manganese oxide, iron phosphide and diammonium hydrogen phosphate are weighed respectively, and 20% of the total weight of glucose is weighed as a carbon source; lithium source, manganese source, iron source and phosphorus source are added with water to reach a solid content of 20%, and wet grinding is performed; 0.5mm zirconia ball is used as grinding medium in wet grinding, the first grinding time is 0.5h, and the grinding speed is 650r / min to obtain precursor slurry; (2) the above-mentioned precursor slurry after grinding is added with carbon source and mixed evenly, and then the second grinding is performed at a grinding speed of 500r / min for 4h, and the solid content is adjusted to 22.1% for spray drying to obtain dry powder; (3) the dried powder is transferred to a tubular sintering furnace, heated to 650℃ under nitrogen atmosphere, sintered at 650℃ for 6h, and naturally cooled to room temperature to obtain lithium manganese iron phosphate material.
[0156] Acquisition of positive electrode composite material: CNT slurry is deposited on the surface of lithium iron manganese phosphate material by atomic layer deposition (ALD) technology to obtain a positive electrode composite material coated with CNTs. The mass ratio of lithium iron manganese phosphate material to CNT in the positive electrode composite material is 100:0.6.
[0157] Preparation of positive electrode sheet: obtain the above-mentioned positive electrode composite material, mix the positive electrode composite material, conductive carbon black, binder PVDF, and carbon nanotube conductive agent in a mass ratio of 96.5:1:2:0.5, add solvent NMP, and stir under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry with a solid content of 55%; coat the positive electrode slurry on aluminum foil to obtain a double-sided coated positive electrode sheet; then dry, roll and cut to obtain a positive electrode sheet.
[0158] The process parameter conditions of the above-mentioned Examples 1-13 and Comparative Examples 1-2 are shown in Table 1 below.
[0159] Table 1
[0160]
[0161] test:
[0162] 1. Testing of positive electrode materials:
[0163] (1) Test of manganese molar ratio a:
[0164] Pretreatment: disassemble the empty lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, wash and dry it to remove the electrolyte and surface side reaction products on the surface of the positive electrode sheet; scrape the positive electrode active material on the surface of the current collector, calcine it at 400°C for 3 hours to remove the binder, etc., to obtain the positive electrode active material powder.
[0165] Test: Accurately weigh 0.5g of positive electrode active material powder, disperse it in 20ml of water, add 10ml of nitric acid, mix well and heat. After the positive electrode active material powder is dissolved, dilute the material to 100ml with water to obtain the test solution;
[0166] The ICP test was conducted on the solution to be tested. The test conditions were as follows: the standard solution was prepared before the test. The standard solution can be used as a normal standard solution only if its concentration linear correlation coefficient is above 0.999. The concentration linear relationship was measured by diluting a 1000 mg / L standard solution with deionized water to different concentrations. The different concentrations are generally 0 mg / 100mL, 1 mg / 100mL, 2 mg / 100mL, 3 mg / 100mL, 5 mg / 100mL, 10 mg / 100mL, 20mg / 100mL, 50 mg / 100mL, 100mg / 100mL, etc.
[0167] Select the element detection spectrum wavelength and set the experimental conditions: according to the characteristics of the sample and the elements to be detected, set the appropriate ICP instrument working conditions; for example: gas flow rate 0.5L / min, power 1150W, select the wavelength of 259.94nm for testing Fe, and select the wavelength of 257.61nm for testing Mn.
[0168] (2) Average length L CNT , Test of primary particle diameter d and porosity c:
[0169] Pretreatment: disassemble the empty lithium-ion battery to obtain the positive electrode sheet, soak the positive electrode sheet in DMC (dimethyl carbonate) at room temperature for 60 minutes, take it out, and dry it at room temperature with a humidity of ≤15% to obtain the treated positive electrode sheet.
[0170] (2.1) Average length L CNTTest: first stick a layer of conductive glue on the sample holder, stick the positive electrode to the sample holder, then coat it with a conductive film, and then observe it under a scanning electron microscope. SEM is magnified to 50,000 times to find agglomerates, and then find CNT materials in the agglomerates. The line drawing method is used to collect the entire length of the CNT. The length of at least 3 CNTs collected at different positions on the page is averaged as L CNT .
[0171] (2.2) Test of primary particle diameter d: First, stick a layer of conductive glue on the sample holder, stick the positive electrode plate on the sample holder, and then coat it with a conductive film, and then observe it under a scanning electron microscope. SEM is magnified to 50,000 times to measure the particle size, and the size of the primary particles inside the agglomerate is measured on the SEM image using the MEARSURENANO software. The primary particle size is collected using the diagonal line method. After the sample size reaches more than 100, the particle size distribution is statistically calculated, and the average value of the primary particle diameter is calculated, which is the primary particle diameter d.
[0172] (2.3) Test of porosity c: Take 10 positive electrode sheets, randomly select 10 areas from each positive electrode sheet, and perform cross-sectional SEM (scanning electron microscope) argon ion polishing CP (SEM-CP, cross-sectional polishing-scanning electron microscope) test, with a magnification of 10,000 times. Each SEM-CP image contains at least 5 spherical aggregates. Use software NanoMeasurer for measurement, where the diameter of the aggregate cross section is R, and the cross section of the pores inside the aggregate is usually a long and narrow structure. The relatively longer distance of the pores in the cross section is the length a, and the relatively shorter distance in the pores is the width b. Then the cross-sectional area of the aggregate S1=π*(R / 2) 2 The area of the pores in the cross section of the agglomerate is S2 = a*b. The porosity of a single agglomerate is S2 / S1*100%. The average value of the accumulated porosity of 50 agglomerates is the porosity c of the active material, and the calculation formula is P=∑S2 / S1 / 50*100%.
[0173] 2. Performance test:
[0174] (1) 45℃ cycle capacity retention test
[0175] At 45°C, the lithium ion secondary batteries prepared in the examples and comparative examples were subjected to cycle performance tests according to the following procedures:
[0176] 1) Charge at a constant current of 1C to 4.25V, and charge at a constant voltage until the current is less than 0.05C, repeat this process for more than 3 times, and record the initial capacity C1 of the battery;
[0177] 2) Charge at a constant current rate of 1C to 4.25V, and charge at a constant voltage until the current is less than 0.05C;
[0178] 3) Let stand for 5 minutes;
[0179] 4) Discharge at 1C rate to 2.5V;
[0180] 5) Let stand for 5 minutes;
[0181] Perform cycle testing according to steps 2)-5) until the lithium-ion secondary battery has been cycled 300 times, and record the capacity C2 of the battery after 300 cycles.
[0182] 45℃ cycle capacity retention rate = C2 / C1*100%.
[0183] (2) DCR test
[0184] 1) Place the battery in a 25°C incubator until thermal equilibrium is reached;
[0185] 2) Charge at a constant current of 1 / 3C to 4.25V, and charge at a constant voltage until the current is less than 0.05C. Repeat this process for more than 3 times and record the battery capacity C1;
[0186] 3) Let stand for 5 minutes;
[0187] 4) Charge the battery to 80% SOC at a 1 / 3C discharge rate;
[0188] 5) Discharge at a current rate of 1C for 18S, record the battery voltage U2 before discharge termination, the current I, and the battery voltage U1 after the battery voltage stabilizes. Calculate the DC internal resistance R1 according to the formula R1=(U2-U1) / I. This R1 is the 25℃ 1C discharge DCR.
[0189] The above test results are shown in Tables 2 and 3 below.
[0190] Table 2
[0191]
[0192] Table 3
[0193]
[0194] From the data of Examples 1-13 and Comparative Examples 1-2 in Tables 2 and 3, it can be seen that: the average length L of the nanotubes CNT The comprehensive control of primary particle diameter d, manganese molar ratio a, and porosity c can improve the internal conductivity of the agglomerate and the kinetic performance of lithium ions. In particular, if 0.09≤a*c / b≤126 is made, a positive electrode material with better internal conductivity and more stable agglomerate structure can be obtained, while taking into account the fast charging performance and cycle performance of the battery. In particular, the length L of the nanotubes CNT, primary particle diameter d, manganese molar ratio a, and porosity c are all set within the range value, which can effectively further improve the cycle performance with relatively good fast charging performance; and, by optimizing the value of a*c / b between 0.6-20, the cycle performance and fast charging performance of the battery can be better.
[0195] Moreover, it can be seen from Examples 1-13 and Comparative Examples 3 and 4 that no CNT is set inside the agglomerate in Comparative Example 3, and CNT is coated on the surface of the agglomerate in Comparative Example 4, and the performance of Comparative Examples 3 and Comparative Examples 4 is worse than that of Examples 1-13; indicating that when no CNT is set inside the agglomerate, or only CNT is set on the surface, it is impossible to improve the conductivity inside the agglomerate, enhance the dynamic performance and cycle stability. The present invention intersperses CNTs between primary particles inside the agglomerate, and controls the average length L of the nanotubes in the agglomerate. CNT The comprehensive relationship of a*c / b among the primary particle diameter d, manganese molar ratio a, and porosity c achieves the effect of improving the kinetic performance and cycle stability.
[0196] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A positive electrode material, It is characterized in that Including chemical formula LiMn x Fe y M (1-x-y) PO 4 Agglomerates, wherein 0.5≤x<1, 0<y≤0.5; M is a doping element, x+y≤1; the agglomerates include primary particles and carbon nanotubes between the primary particles; the agglomerates satisfy the following relationship: 0.09≤a*c / b≤126;b=L CNT / d; Wherein, a is the molar ratio of manganese in the aggregate to the total amount of ferromanganese; c is the porosity of the aggregate, in units of %; d is the diameter of the primary particle, in units of nm; L CNT is the average length of carbon nanotubes in the aggregate, in nm; The value of a is 0.5-0.96; The value of c is 5-35; The value of b is 0.25-50.
2. The positive electrode material according to claim 1, It is characterized in that The value of a*c / b is 0.6-20.
3. The positive electrode material according to claim 2, It is characterized in that The value of a is 0.6-0.85; And / or, the value of c is 10-25; And / or, the value of b is 1-13.
4. The positive electrode material according to any one of claims 1 to 3, It is characterized in that The L CNT 100nm-1000nm; And / or, the d is 20nm-400nm.
5. The positive electrode material according to claim 4, It is characterized in that The L CNT 200nm-800nm; And / or, the d is 40nm-200nm.
6. A positive electrode sheet, It is characterized in that The positive electrode material comprises the positive electrode material according to any one of claims 1 to 5.
7. The positive electrode sheet according to claim 6, It is characterized in that The positive electrode sheet also includes a positive electrode conductive agent, and the positive electrode conductive agent is selected from one or more of conductive carbon black and carbon nanotubes.
8. The positive electrode sheet according to claim 7, It is characterized in that The positive electrode conductive agent is selected from conductive carbon black.
9. An electrochemical device, It is characterized in that A positive electrode sheet comprising any one of claims 6 to 8.
10. An electrical device, It is characterized in that An electrochemical device comprising the electrochemical device according to claim 9.
